AB0402 DISEASE ACTIVITY AND OBSESSIVE-COMPULSIVE DISORDER IN SYSTEMIC LUPUS ERYTHEMATOSUS. (2nd June 2020) - Barraclough, M.; Parker, B.; Mckie, S.; Pemberton, P.; Jackson, A.; Elliott, R.; Bruce, I. N.
Abstract : Background: Obsessive-compulsive disorder (OCD) is more prevalent in systemic autoimmune diseases when compared to healthy controls. This is in part due to inflammatory mechanisms, common across both conditions. Neuroinflammation and specifically problems within the basal ganglia are associated with OCD. Objectives: The primary objective of this analysis was to investigate the effects of disease activity in systemic lupus erythematosus (SLE) on OCD. Other variables investigated included psychiatric aspects, inflammatory biomarkers and structural brain abnormalities. Methods: SLE patients who met ACR or SLICC criteria were recruited. Demographic and clinical data were collected and data measuring disease activity (BILAG and SLEDAI-2K), disease damage (SLICC-DI), depression (MADRS, BDI-II, HADS), anxiety (HADS, STAI), fatigue (FSMC), quality of life (LupusQoL and EQ5D), inflammatory and endothelial activation (EA) biomarkers (IL-6, ESR, TNF-α, MCP-1, hsCRP, BLyS, VCAM-1, VEGF, EMVs) and OCD (OCI-R). MRI FLAIR structural scans were also used to examine signal hyperintensities in the brain. Participants with active disease (SLE-F) also had a 2 nd visit approx. 4 months later. Non-parametric correlations with the OCI-R were undertaken for all SLE participants and for the change over time scores for the SLE-F participants (n=11). Results: 39 participants were included in the analysis and were typical for a SLE population. 6 (23%) patients had scores above the threshold for OCD. OCI-R significantly correlated with disease activity, quality of life, fatigue, depression and anxiety measures for all the SLE participants. Change in monocyte chemoattractant protein-1 (MCP-1) correlated with the OCI-R for the within SLE-F group analysis (Table 1 ). No significant correlations were found with the full SLE group for inflammatory or EA biomarkers or with either group for the structural brain analysis. Conclusion: OCD in lupus is strongly related to other psychological co-morbidities, fatigue and quality of life. Our results also support a role for inflammatory pathways in mediating some of these changes and so obsessive-compulsive features should be assessed in SLE patients who flare. A larger study is underway to better understand the mechanisms underlying these associations. Acknowledgments: This study was partially funded by an unrestricted grant from Sanofi Genzyme and supported by the NIHR Manchester Biomedical Research Centre. Disclosure of Interests: Michelle Barraclough Grant/research support from: This study was partially funded by an unrestricted grant from Sanofi Genzyme., Ben Parker Grant/research support from: GSK and Sanofi Genzyme, Consultant of: GSK, AstraZenaca, UCV, Abbvie, Pfizer, BMS, Celltrion, Shane McKie: None declared, Philip Pemberton: None declared, Alan Jackson: None declared, Rebecca Elliott: None declared, Ian N. Bruce Grant/research support from: Genzyme Sanofi, GSK, and UCB, Consultant of: Eli Lilly, AstraZeneca, UCB, Iltoo, and Merck Serono, Speakers bureau: UCB